DESIGNING THE SHAPE OF A NOSE CLIP FOR A HALF-FACE MASK USING 3D ANTHROPOMETRIC FACE ANALYSIS: Half-face mask with 3D anthropometry - Tjolleng, Amir; Chang, Joonho; Park, Jangwoon; Jung, Kihyo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This study designed the shape of a nose clip for a half-face mask by considering 3D facial contours. 3D facial scan data for 60 participants (mean age = 23.8 ± 2.0 years old) were collected. Three facial shapes were identified in a cluster analysis based on the facial dimensions: small (3.3%), medium (88.3%), and large (8.3%). The medium group, with the largest accommodation, was selected as the shape of the nose clip. Next, a virtual fitting test for a digital prototype with the nose clip shape was conducted to evaluate to the match with participants’ facial contours. Lastly, a half-face mask with the novel nose clip was compared to a half-face mask without the nose clip in terms of subjective satisfaction and humidity level caused by air leaking. The half-face mask with the nose clip achieved better performance for both subjective satisfaction (4.9 out of 7) and humidity level (9.4%).